385 A Double Blind, Randomized Controlled Trial on the Resuscitation of Preterm Infants with 30% Versus 65% Oxygen at Birth. (October 2012) - Rook, D; Vlaardingerbroek, H; Schierbeek, H; Eijk, AC van der; Escobar, J; Longini, M; Buonocore, G; Vento, M; Goudoever, JB van; Vermeulen, MJ
Abstract : Background: Resuscitation of term infants at birth with 100% oxygen increases oxidative stress with concomitant deleterious effects. Optimal levels for preterm infants are unknown. We hypothesized that resuscitation of preterms with initial FiO2 of 30% is safe, decreases oxidative stress and improves outcome compared to an initial FiO2 of 65%. Design: Preterm infants (GA<32 weeks) were randomized to start resuscitation after birth with 30% or 65% oxygen. FiO2 was adjusted based on oxygen saturation and heart rate. Primary outcome was survival without bronchopulmonary dysplasia (BPD) at 36 weeks postmenstrual age. Oxidative stress was determined by urinary DNA and protein oxidation markers, and plasma non protein bound iron. Results: We included 194 infants, mean GA (28 4 /7 ±2 1 /7 weeks) and birth weight (1076±347 gram) were not different between groups. FiO2 was significantly different during the first 5 minutes following birth. Clinical outcomes (table) and oxidative stress markers were not statistically different between groups. Conclusion: Resuscitation of preterm infants at birth with 30% oxygen is as safe as resuscitation with 65%, but does not offer benefits with regard to survival without BPD.